A New Concept of Techno-Economic Institutions within Institutional Economics: Integrating Technologies and Institutional Frameworks - Shkalenko, Anna V.; Kozlova, Svetlana A. (Emerging Science Journal, 2024)
This study investigates the concept of techno-economic institutions within institutional economics, focusing on the integration of technologies into economic frameworks to foster development. The primary objective is to introduce and advocate for the novel concept of “techno-economic institutions,” which is essential for embedding technologies into the socio-economic environment. This research employs a comprehensive methodological approach, including theoretical analysis, literature review, comparative studies, and case studies, to develop a new analytical model and provide fresh insights. The key findings include a comparative analysis of the interplay between institutions and technologies, a variational model detailing the life cycles of General-Purpose Technologies (GPTs), and an in-depth examination of institutional roles. The econometric models developed in this study demonstrate the significant impact of ICT patents and SCM systems on government efficiency, empirically validating the proposed theoretical framework. This paper contributes to the academic discourse by offering a methodologically robust and empirically substantiated examination of technological advancements in institutional frameworks, highlighting the importance of flexible institutional structures capable of adapting to technological change. These insights provide actionable recommendations for policymakers and suggest strategic investments in technological infrastructure to enhance government performance. Future research should explore the generalizability of these findings in different institutional contexts and examine variability in technology-institution interactions across diverse geopolitical landscapes. Doi: 10.28991/ESJ-2024-08-05-022 Full Text: PDF